2021
DOI: 10.7202/1075671ar
|View full text |Cite
|
Sign up to set email alerts
|

Physical Restraint, Seclusion, and Time-Out Rooms in Canadian Schools: Analysis of a Policy Patchwork

Abstract: The intended purpose of physical restraint, seclusion, and time-out rooms in schools is to intervene in a crisis when the behaviour of a student poses an immediate or imminent, and significant threat to physical safety. While the use of physical restraint, seclusion, and time-out rooms is intended to provide protection from immediate physical harm, there is increasing concern that these practices are being used more broadly and that individuals with disabilities are disproportionately subjected to their use. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The need for regulation of the use of physical restraint, seclusion, and time-out rooms in Canadian educational jurisdictions was affirmed in a recent policy analysis conducted by Bartlett and Ellis (2021). This analysis found that seven educational jurisdictions (Manitoba, Northwest Territories, Ontario, Quebec, Nunavut, Saskatchewan, and Yukon) did not have provincial/territorial educational policies or support documents that specifically regulate or provide guidance regarding the use of physical restraint, seclusion, and time-out rooms in schools.…”
Section: Restraint Seclusion and Time-out In Canadamentioning
confidence: 99%
See 2 more Smart Citations
“…The need for regulation of the use of physical restraint, seclusion, and time-out rooms in Canadian educational jurisdictions was affirmed in a recent policy analysis conducted by Bartlett and Ellis (2021). This analysis found that seven educational jurisdictions (Manitoba, Northwest Territories, Ontario, Quebec, Nunavut, Saskatchewan, and Yukon) did not have provincial/territorial educational policies or support documents that specifically regulate or provide guidance regarding the use of physical restraint, seclusion, and time-out rooms in schools.…”
Section: Restraint Seclusion and Time-out In Canadamentioning
confidence: 99%
“…Only Alberta, Newfoundland, and Prince Edward Island were found to have Ministerial Directives, Operational Procedures, or policies that were explicitly directive and enforceable; however, even within these mandates, specific practices (e.g., physical restraint as compared to time-out rooms) were subject to varying degrees of enforceability. For example, the province of Newfoundland mandates how physical restraint must be addressed but provides only non-directive guidelines regarding the use of time-out rooms (Bartlett & Ellis, 2021).…”
Section: Restraint Seclusion and Time-out In Canadamentioning
confidence: 99%
See 1 more Smart Citation